Como conchas à beira-mar : fragmentos de vida - Souza, Kamila Vilela (2019)
We walk through the city, have a coffee on the balcony, meet lives that Society has tried to erase. Lives marked by manicomial hospitalizations and which have been silenced for many years. During weekly meetings in a house in the city of Cariacica – ES we talked to some gentlemen and in some moments, listened to their life stories, generally fragmented narratives made of vestiges and in this text, we narrate them: they are our shells. Amateurishly we photograph pieces, rests, and expressions. Like a nautical chart, we mark brief points in history, showing the moment when the medicine tries to appropriate madness and passes to consider it a mental illness. We compose together, we mix and we fell. Here we present a few words that narrates lives, which narrates histories, which narrate the everyday. We inhabited this house, but we also walked, because we understand the city as a place of potency, of creation and deconstruction – we are walkers along the beach. Yes, the beach, but precisely the water that followed us in this journey. The waves guide us, the sea strengthens us, the sand takes us from comfort.